Decreased Intestinal Microbiome Diversity in Pediatric Sepsis: A Conceptual Framework for Intestinal Dysbiosis to Influence Immunometabolic Function. (17th March 2021) - Weiss, Scott L.; Bittinger, Kyle; Lee, Jung-Jin; Friedman, Elliot S.; Mattei, Lisa M.; Graham, Kathryn; Zhang, Donglan; Bush, Jeny; Balamuth, Fran; McGowan, Francis X.; Bushman, Frederic D.; Baldassano, Robert N.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: The intestinal microbiome can modulate immune function through production of microbial-derived short-chain fatty acids. We explored whether intestinal dysbiosis in children with sepsis leads to changes in microbial-derived short-chain fatty acids in plasma and stool that are associated with immunometabolic dysfunction in peripheral blood mononuclear cells. Design: Prospective observational pilot study. Setting: Single academic PICU. Patients: Forty-three children with sepsis/septic shock and 44 healthy controls. Measurements and Main Results: Stool and plasma samples were serially collected for sepsis patients; stool was collected once for controls. The intestinal microbiome was assessed using 16S ribosomal RNA sequencing and alpha- and beta-diversity were determined. We measured short-chain fatty acids using liquid chromatography, peripheral blood mononuclear cell mitochondrial respiration using high-resolution respirometry, and immune function using ex vivo lipopolysaccharide-stimulated whole blood tumor necrosis factor-α. Sepsis patients exhibited reduced microbial diversity compared with healthy controls, with lower alpha- and beta-diversity. Reduced microbial diversity among sepsis patients (mainly from lower abundance of commensal obligate anaerobes) was associated with increased acetic and propionic acid and decreased butyric, isobutyric, and caproic acid. Decreased levels of plasma butyric acid were further associated with lower peripheral blood mononuclear cell mitochondrial respiration, which in turn, was associated with lower lipopolysaccharide-stimulated tumor necrosis factor-α. However, neither intestinal dysbiosis nor specific patterns of short-chain fatty acids were associated with lipopolysaccharide-stimulated tumor necrosis factor-α. Conclusions: Intestinal dysbiosis was associated with altered short-chain fatty acid metabolites in children with sepsis, but these findings were not linked directly to mitochondrial or immunologic changes. More detailed mechanistic studies are needed to test the role of microbial-derived short-chain fatty acids in the progression of sepsis.